Understanding Nonverbal Communication Among TNI (Indonesian National Army) Members in Everyday Life - Amaliah Ramdani; Syarifuddin Dollah; Geminastiti Sakkir (PT ARRUS Intelektual Indonesia, 2024)
This research focuses on how nonverbal communication is important in the military, particularly among members of the TNI in their neighbourhoods. The researcher used interviews to collect data using open-ended questions. The researcher identified that saluting is more than just a greeting; it shows respect for superiors and tradition, which promotes a disciplined and united military community. The research underlined the adaptation of nonverbal communication, especially hand signals, in operational settings for efficient and silent exchange of information. In summary, nonverbal cues, such as saluting, play a huge role in keeping the military community disciplined and united for successful operations.